Monitoring of Antibiotic-Induced Alterations in the Human Intestinal Microflora and Detection of Probiotic Strains by Use of Terminal Restriction Fragment Length Polymorphism - Jernberg, Cecilia; Sullivan, Åsa; Edlund, Charlotta; Jansson, Janet K (APPLIED AND ENVIRONMENTAL MICROBIOLOGY, 2005)
Terminal restriction fragment length polymorphism (T-RFLP) was investigated as a tool for monitoring the human intestinal microflora during antibiotic treatment and during ingestion of a probiotic product. Fecal samples from eight healthy volunteers were taken before, during, and after administration of clindamycin. During treatment, four subjects were given a probiotic, and four subjects were given a placebo. Changes in the microbial intestinal community composition and relative abundance of specific microbial populations in each subject were monitored by using viable counts and T-RFLP fingerprints. T-RFLP was also used to monitor specific bacterial populations that were either positively or negatively affected by clindamycin. Some dominant bacterial groups, such as Eubacterium spp., were easily monitored by T-RFLP, while they were hard to recover by cultivation. Furthermore, the two probiotic Lactobacillus strains were easily tracked by T-RFLP and were shown to be the dominant Lactobacillus community members in the intestinal microflora of subjects who received the probiotic.